IMPLEMENTASI MANAJEMEN PEMBELAJARAN RAMAH ANAK DALAM MENANAMKAN KARAKTER DISIPLIN (STUDI PADA UPAYA GURU KELAS 1A DI MI MUHAMMADIYAH BEJI) - Zuri Pamuji (Jurnal Penelitian Agama, 2017)
Abstract: Child-friendly learning management is intended with the implementation of management functions in the form of planning, organizing, directing, and controlling in the learning process with regard to the rights of children and without any act of violence in the process implementation of all management functions. Based on the result of the research, the implementation effort is done by using the cycle of learning management function, starting from planning, organizing, directing and controlling of learning. Where in each of the learning management functions, there are various activities to incorporate child-friendly elements and integrate with the inculcation of discipline character for students, especially related to activities before learning, in the learning process and at the end of the learning process. Keywords: the character of discipline, management of learning, child-friendly